Does contemporary photography have a history? (Palíndromo, 2015)
In this article, Michel Poivert sets out some issues addressed in the book Photographie contemporaine, first published in 2012 and reissued and expanded in 2010. He updates his observations on contem- porary photography, this phenomenon that undergoes constants changes.